‘Een filosofisch geschriftje’: Christiaan Huygens’ gedachten over God in zijn Cosmotheoros en andere geschriften - Smit, Nienke (Studium, 2014)
Although much has been written about Christiaan Huygens (1629–1695), his religious views are almost neglected in historical research. Some scholars have come to the conclusion that God played no part at all in the worldview of this great mathematician. Although Huygens has never written a book exclu- sively devoted to the subject of God, he did leave us some notes in which he explicitly expresses his views about God and the divine. This article focuses on Huygens’ philosophical writings and especially on his last completed work Cosmotheoros (1698), in which he discusses the possibility of extra-terres- trial life. In this book God is an important subject. Huygens’ thoughts show a strong belief in an underlying logic behind the construction of the universe. According to Huygens, the idea that the earth is just a planet among other planets, logically implies that these other planets should have a similar nature as the earth and are inhabited by ‘rational beings’. Eve- rything in the universe is created for a reason, so God would not have created anything for no purpose. Huygens can’t imagine the world being created without a great intelligent deity, but he denies that God has a direct influence on the course of events on earth. Therefore, in his view, the existence of miracles is impossible. This article presents a new perspective on Christiaan Huygens and shows that the concept of God was actually a crucial element in his understanding of the world.